Treatment patterns of chronic obstructive pulmonary disease in employed adults in the United States - Diette, Gregory B (Int J Chron Obstruct Pulmon Dis, 2015)
BACKGROUND: This study evaluated patterns of pharmacotherapy in chronic obstructive pulmonary disease (COPD) as they relate to recommended guidelines in a prevalent COPD patient population with employer-sponsored health insurance in the US. METHODS: Health care claims data from 2007 and 2008 were retrospectively analyzed for the study population defined as patients aged 40 years and older, continuously enrolled during the study period, and having at least one inpatient or one emergency department (ED) visit, or at least two outpatient claims coded with COPD (International Classification of Diseases, 9th Revision, Clinical Modification code 491.xx, 492.xx, 496.xx). Rates of any pharmacotherapy (both maintenance and reliever), long-acting maintenance pharmacotherapy in patients with an exacerbation history, and short-term treatment of acute exacerbations of COPD were evaluated in the overall population, newly diagnosed, and previously diagnosed patients (including maintenance-naïve and maintenance-experienced). Stratified analyses were also conducted by age group (40–64 years, ≥65 years) and physician specialty. RESULTS: A total of 55,361 patients met study criteria of whom 39% were newly diagnosed. The mean age was 66 years, and 46% were male. Three-fourths (74%) of all COPD patients had some pharmacotherapy (maintenance or reliever) with less than half (45%) being treated with maintenance medications. The combination of an inhaled corticosteroid and a long-acting beta-agonist was the most prevalent drug class for maintenance treatment followed by tiotropium. Only 64% of patients with an exacerbation history had a prescription for a long-acting maintenance medication, and short-term treatment with oral corticosteroids or antibiotics was higher for hospitalization exacerbations compared to ED visit exacerbations (68% vs 44%). In general, the rates of pharmacotherapy were highest in patients who were maintenance-experienced followed by newly diagnosed and maintenance-naïve. CONCLUSION: The majority of COPD patients received maintenance or reliever COPD medications, but less than half received guideline-recommended care, especially those with an exacerbation history or receiving short-term treatment for acute exacerbations.